2018
DOI: 10.33182/ml.v15i1.339
|View full text |Cite
|
Sign up to set email alerts
|

Family configurations and arrangements in the transnational mobility of early-career academics: Does gender make twice the difference?

Abstract: Previous studies have pointed out the highly gendered character of academia in general and international mobility in particular: women academics are confronted with a ‘glass ceiling’, and they are less geographically mobile than men, mainly as a result of family obligations. This paper examines whether gender plays twice a role in how women and men consider family arrangements in regard to a long-term post-PhD period of transnational mobility. Using data from an online survey and face-to-face interviews at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In this paper, we have identified and explored many facets of academic mobility of males and females that relate to 1) mobility differences across nationalities, disciplines, and career stages, 2) the international mobility flow 3) the factors that associate with mobility, 4) relationship between mobility and scholars' publications and citations, 5) different position of mobile and non-mobile scholars in their collaboration network. Our findings regarding the first research question revealed that in the world of academia, international mobility of women is less than men, which is consistent with the past studies (Jöns, 2011;Leemann, 2010;Myers & Griffin, 2019;Toader & Dahinden, 2018). We observe that the mobility score of both genders has the lower level in the early and mid-career stage, which can be related to the time that families should focus more on preschool children than going abroad.…”
Section: Discussionsupporting
confidence: 91%
“…In this paper, we have identified and explored many facets of academic mobility of males and females that relate to 1) mobility differences across nationalities, disciplines, and career stages, 2) the international mobility flow 3) the factors that associate with mobility, 4) relationship between mobility and scholars' publications and citations, 5) different position of mobile and non-mobile scholars in their collaboration network. Our findings regarding the first research question revealed that in the world of academia, international mobility of women is less than men, which is consistent with the past studies (Jöns, 2011;Leemann, 2010;Myers & Griffin, 2019;Toader & Dahinden, 2018). We observe that the mobility score of both genders has the lower level in the early and mid-career stage, which can be related to the time that families should focus more on preschool children than going abroad.…”
Section: Discussionsupporting
confidence: 91%
“…Committing to this requirement involves sacrificing principles associated with the industrial convention that allow predictability, the possibility of planning and orientation towards the long term. This also weakens values related to the civic convention, such as human equality, since the impossibility of planning an academic career and the uncertainties involved in pursuing one disadvantage especially women and junior researchers from non-academic families (Leemann, 2010; Leemann and Boes, 2015; Toader and Dahinden, 2018). The governance principles of the ERA are thus more closely tailored to men of an academic family background and involve exclusionary power.…”
Section: Resultsmentioning
confidence: 99%
“…Demands derived from this observation, such as installing gender equality officers at universities and research organisations, have brought this criticism to public attention and address the level of orders of justification (Toader and Dahinden, 2018).…”
Section: Governing Principles In the European Research Area: Barriersmentioning
confidence: 99%
“…While, with the first couple, mobility is shown to be highly gendered, I also argue that temporal perspectives illuminate how mobility can be more varied and complex than 'men as the primary or lead migrant' and 'women as the tied migrant'. There are moments of contestation and renegotiation even when situated within traditional/patriarchal structures of social life (Toader & Dahinden, 2018). Decision-making is complex and continually shifts along this spectrum as a result of intra-family circumstances and priorities as well as the conditions of migration policy in various destination countries.…”
Section: Discussionmentioning
confidence: 99%